The Use of Six Sigma as A Blood Glucose Quality Control Evaluation in UPTD Health Laboratory of Bandung City - Wahyu, Cep; Kafes, Ally; Karwati, Siti (Jurnal Biologi Tropis, 2025)
Six sigma is a statistical analysis method that involves calculations through CV, TEa, and bias values that describe the precision and accuracy of the examination. This study aims to analyze the evaluation of blood glucose examination quality control using six sigma at the Bandung City Health Office Laboratory UPTD. This study uses descriptive research to determine the precision, accuracy, and sigma value of the results of quality control of blood glucose examinations on the Cobas C311 Chemistry Analyzer as material for quality control evaluation in clinical laboratories. The results of the study on the accuracy (d%) and precision (CV%) of the quality control of blood glucose examinations on the Cobas C311 Chemistry Analyzer at the Bandung City Health Office Laboratory UPTD are quite good because the values obtained do not exceed the maximum limit. The results of the performance of the Cobas C311 Chemistry Analyzer on blood glucose examinations at the Bandung City Health Office Laboratory UPTD are considered quite good because the TE value < TEa (CLIA) is obtained. The six sigma value of blood glucose examinations on the Cobas C311 Chemistry Analyzer is obtained 3 sigma which indicates "marginal" where the combination of random errors and systematic errors is still tolerable.